Dlaczego nie przekonują nas przekonywające argumenty - Tokarz, Marek (Filozofia Nauki, 2007)
Sometimes, very often in fact, our persuasive efforts fail even though we are right and the arguments we use are logically correct. In the article we are trying to tell why this is so, and as it turns out there may be quite a few causes. First, the hearer may not be convinced because he has not been motivated to try and understand the speaker - understanding takes work, and as a rule we do not like to work. Or he may not be convinced because he does not like the speaker himself. There are also many other potential causes, such as: balancing cognitive dissonance, faulty attributions, phenomena of assimilation and contrasting, or psychological mechanisms of consequence, conformism and reactance.